Hyperbranched dendritic nano-carriers for topical delivery of dithranol. (May 2013) - Agrawal, Udita; Mehra, Neelesh Kumar; Gupta, Umesh; Jain, N. K.
Abstract The purpose of the current investigation was to explore the potential of polypropylene imine (PPI) dendrimers to deliver dithranol (DIT) topically and to evaluate its encapsulation, permeation and skin irritation potential. PPI (5.0 generation, 5.0 G) dendrimers and DIT-loaded PPI (DIT–PPI) were prepared and characterized by spectroscopy and transmission electron microscopy. DIT encapsulation, in vitro skin permeation study, skin irritation studies, fluorescent studies and tape stripping studies were performed. Loading of DIT was found to be pH dependent with maximum encapsulation at acidic pH (1.0 ± 0.02, 17.2 ± 0.56 and 57.1 ± 1.32% at 7.4, 5.5 and 1.2 pH, respectively). DIT–PPI showed significantly enhanced permeation rate constant and lesser skin irritation (11.61 ± 1.80 μg/cm2/h and 1.0, respectively) when compared with the plain DIT solution (2.72 ± 0.31 μg/cm2/h and 2.3, respectively). Skin separation studies and confocal laser scanning microscope images showed that the dye-loaded dendrimers exhibits deposition of dye in pilosebaceous compartment. These studies demonstrate that PPI can be exploited to improve the topical bioavailability of the molecules in a controlled pattern. The enhanced accumulation of DIT via dendrimer carrier within the skin might help optimize targeting of this drug to the epidermal and dermal sites, thus creating new opportunities for well-controlled, modern topical application of DIT for the treatment of psoriasis.